PEMBUATAN SOFTWARE MONITORING JUMLAH PRODUKSI KERUPUK MENGGUNAKAN BORLAND DELPHI 7.0 - Adiyani C, Mirsari; Danusaputro, Hernowo (BERKALA FISIKA, 2011)
The monitoring program for the crackers counter has been done by Borland Delphi 7.0. The results of this program is intended to help the manager’s job in monitorin the amount ofcracker produced by industry. This program using Borland Delphi 7.0. While to find out the cracker pieces which fellfrom the conveyor using photodiodes sencors and lasers as light sources directed at the sensorphotodiodes. When the sencor detected a cracker pieces which fell from the conveyor, the sensorsend a signal to the microcontroller for processing and then send to computer via serialcommunication. On computer, that data is received by Borland Delphi 7.0 program to displayedand stored in Microsoft Access. The system has been realized successfully and can printer the data stored in databases sothat the amountof crackers produced will be known.Keyword: Crackers, Borland Delphi 7.0, Microsoft Access, photodiodes sencors, lasers